Chinese medicine interventions for cerebral small vessel disease-related cognitive impairment: a systematic review and meta-analysis - Miaomiao Zhao; Xiangyi Zheng; Yulin Mu; Genming Zhang; Xinxing Lai (Frontiers in Pharmacology, 2026)
Background Cerebral small vessel disease–related cognitive impairment (CSVD-CI) is a common and clinically important challenge of cerebral small vessel disease, but effective therapeutic options remain limited. Chinese medicine interventions (CMIs) may be beneficial, although the evidence is uncertain. Purpose To evaluate the efficacy and safety of CMIs for adults with CSVD-CI and assess evidence certainty. Study design Systematic review and meta-analysis of randomized controlled trials. Methods Eight databases were systematically searched from inception to 31 December 2025. Primary outcomes were cognitive function, mainly assessed by the Montreal Cognitive Assessment (MoCA) and Mini-Mental State Examination (MMSE). Secondary outcomes included total effective rate, Traditional Chinese Medicine syndrome score, selected biochemical and hemorheological indicators, and adverse events (AEs). Risk of bias was assessed using the Cochrane Risk of Bias tool, and certainty of evidence was evaluated using GRADE. Results Fifty RCTs involving 4,454 participants were included. Compared with conventional therapy alone, CMIs plus conventional therapy were associated with higher end-of-treatment MoCA and MMSE scores, and the pooled incidence of AEs did not differ significantly between the intervention and control groups. The overall risk of bias was predominantly unclear, whereas the certainty of evidence was low or very low. Conclusion CMIs were associated with higher end-of-treatment cognitive scores; however, extreme heterogeneity, unclear risk of bias, and low evidence certainty substantially limit confidence in these findings. Available data are insufficient to establish long-term efficacy or safety. Multicenter, prospectively registered RCTs with standardized diagnostic criteria, intervention reporting, outcome selection, and safety monitoring are required. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/view/CRD420251176394 , identifier, CRD420251176394.